Analysis Of The Use Of An Arduino-Based Non-Physical Contact Thermometer - Rery Geffrey Benson (International Journal of Industrial Innovation and Mechanical Engineering, 2024)
Human body temperature can be measured using a clinical thermometer. Currently, there are various types of thermometers used, including analog thermometers and digital thermometers. Usually, this tool takes about one to two minutes to produce accurate body temperature values. However, there are problems with availability and a significant increase in demand during the pandemic, making these tools difficult to find. In this research, a device was created that can measure human body temperature quickly and provide accurate readings. This device uses an MLX90614 series infrared sensor integrated with an Arduino Uno, ultrasonic sensor, buzzer, LED, and 16x2 LCD screen to create a body thermometer without physical contact. The research method used involves data collection, needs analysis, hardware and software design, and testing to ensure that the device runs as expected.